ANALISA HUJAN-DEBIT PADA DAERAH ALIRAN SUNGAI (DAS) KALI LAMONG DENGAN METODE HSS ITB-I - Halim Pranata; Nur Azizah Affandy (Fakultas Teknik, Universitas Wiraraja, 2021)
Estimation of flood hydrograph in a river is the main thing done in the planning of a water building. In a river that does not have discharge measurement data for a long time, the method of converting from rain to river discharge is a common thing to do to get design flood discharge. Until now, the synthetic unit hydrograph method (HSS) is still a tool used in design flood discharge analysis. This study applies the Debit Rain Analysis in the Kali Lamong River Basin with the HSS ITB-I Method. In calculating the flood discharge plan also requires an appropriate method to describe the flood hydrograph of a watershed. The Kali Lamong River Basin is a Bengawan Solo tributary, which is the longest river in Java. In this study the ITB-I method will be used. The results of this study were obtained flood discharge obtained in the 2-year return period of Q 10705.56 m3/ second. Peak discharge occurs at 14.00 hours at Qp 463.29 m3/ second and returns to base flow at 60.00 hours. Flood discharge obtained in the return period of 5 years is Q 12308.43 m3/ second. Peak discharge occurs at 14.00 hours at Qp 532.66 m3/ second and returns to base flow at 60.00 hours. Flood discharge obtained in the 10 year return period is Q 13154.62 m3/ second. Peak discharge occurs at 14.00 hours at Qp 569.28 m3/ second and returns to base flow at 60.00 hours. Flood discharge obtained in the 25 year return period is Q 14056.51 m3/ second. Peak discharge occurs at 14.00 hours at Qp 608.31 m3/ second and returns to base flow at 60.00 hours. Flood discharge obtained in the 50 year return period is Q 14634.82 m3/ second. The peak discharge occurs at 14.00 hours at Qp 633.34 m3/ second and returns to the base flow at 60.00 hours and the flooding obtained at the 100 year return period is Q 15148.26 m3/ second. Peak discharge occurs at 14.00 hours at Qp 655.56 m3/ second and returns to base flow at 60.00 hours.